Nanostructured Lipid Carrier–Mediated Transdermal Delivery of Aceclofenac Hydrogel Present an Effective Therapeutic Approach for Inflammatory Diseases - Garg, Neeraj K.; Tandel, Nikunj; Bhadada, Sanjay Kumar; Tyagi, Rajeev K. (Frontiers in Pharmacology, 2021)
Aceclofenac (ACE), a cyclooxygenase-2 inhibitor, is the derivative of the diclofenac group that has been in use for the symptomatic treatment of systemic inflammatory autoimmune disease, rheumatoid arthritis (RA). Partial solubility, high lipophilic nature, and stability challenge its use in developing topical formulations. Hence, we developed and characterized nanostructured lipid carrier (NLC)–based ACE (ACE-NLC) hydrogel for an efficient transdermal delivery. NLC microemulsion was prepared using different lipids by various methods and was characterized with respect to particle size, zeta potential, surface morphology, and drug encapsulation efficiency. The optimized NLC formulation was incorporated into Carbopol® 940 gel, and this arrangement was characterized and compared with the existing marketed gel (Mkt-gel) formulation to assess in vitro drug release, rheology, texture profile, in vivo skin retention and permeation, and stability. Furthermore, prepared and characterized ACE-loaded NLC formulation was evaluated for skin integrity and fitted in a dermatokinetic model. The results of this study confirmed the spherical shape; smooth morphology and nanometric size attested by Zetasizer and scanning and transmission electron microcopy; and stability of the ACE-NLC formulation. The ACE-NLC-gel formulation showed good rheological and texture characteristics, and better skin distribution in the epidermis and dermis. Moreover, ACE-NLC permeated deeper in the skin layers and kept the skin integrity intact. Overall, NLC-based gel formulation of ACE might be a promising nanoscale lipid carrier for topical application when compared with the conventional Mkt-gel formulation.